Biodiversity of the ichthyofauna in the estuary area of Padang, West Sumatra, Indonesia - ENI KAMAL; AMELIA SRIWAHYUNI LUBIS; ZAVIRA MAYZURI; RINI HERTATI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kamal E, Lubis AS, Mayzuri Z, Hertati R. 2025. Biodiversity of the ichthyofauna in the estuary area of Padang, West Sumatra, Indonesia. Biodiversitas 26: 2621-2630. Estuaries are transitional ecosystems between marine and terrestrial environments, characterized by high biodiversity and a crucial role in maintaining aquatic ecosystems. This study aimed to identify the diversity, distribution patterns, and environmental influences on ichthyofauna in the estuaries of Padang, West Sumatra, Indonesia. Fish sampling was conducted in five estuarine sites from July to December 2024 using habitat-specific fishing gear, while water quality parameters, including temperature, salinity, pH, and dissolved oxygen, were measured in situ. Data analysis included species identification, Shannon-Wiener Diversity Index, Evenness Index, Simpson Dominance Index, and correlation and regression tests to evaluate the relationship between environmental factors and ichthyofauna biodiversity. Results indicate varying fish distribution across sites, with Teluk Buo exhibiting the highest diversity (H': 3.27), while the Batang Arau River Estuary showed species dominance and low diversity. The highest Evenness Index was recorded in the Batang Arau and Anai River Estuaries, where the highest Simpson Dominance Index was found in the Anai River and Batang Arau estuaries, primarily dominated by Rasbora sp. (28 individuals) and Ambassis tetra (21 individuals). Fish distribution was influenced by environmental factors such as food availability, habitat complexity, water quality, and interspecies interactions. More structurally complex habitats supported higher biodiversity, while disturbances like pollution, overfishing, and habitat degradation led to species dominance and reduced biodiversity.